2012
DOI: 10.1371/journal.ppat.1003051
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Signaling Is Linked to a Hypermigratory Phenotype in Dendritic Cells Infected by Toxoplasma gondii

Abstract: During acute infection in human and animal hosts, the obligate intracellular protozoan Toxoplasma gondii infects a variety of cell types, including leukocytes. Poised to respond to invading pathogens, dendritic cells (DC) may also be exploited by T. gondii for spread in the infected host. Here, we report that human and mouse myeloid DC possess functional γ-aminobutyric acid (GABA) receptors and the machinery for GABA biosynthesis and secretion. Shortly after T. gondii infection (genotypes I, II and III), DC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
271
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(288 citation statements)
references
References 69 publications
14
271
0
3
Order By: Relevance
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact mechanism by which latent toxoplasmosis affects behaviour is unclear, T. gondii can exist intracellularly in the brain throughout the life of the host (Carruthers and Suzuki 2007), potentially modifying neural structure or function (Berenreiterová et al 2011, Prandovszky et al 2011, Fuks et al 2012. Indeed, T. gondii appears to alter dopamine metabolism (Parlog et al 2015), with the potential to substantially increase dopamine concentration in the brain (Berenreiterová et al 2011).…”
mentioning
confidence: 99%
“…Although dendritic cells are considered guardians of the immune system, they can also, paradoxically, mediate in the spread of the parasite. This mechanism is produced by the induction in these cells of the GAD enzyme and therefore of GABA production and secretion, which in turn activate GABA receptors expressed by these same cells, stimulating their motility [137]. In experimental mouse models, inhibition of the GABAergic pathway by blockade of GABAA receptors or inhibition of the GAD enzyme markedly reduced the hypermotility and spread of T. gondii-infected dendritic cells and therefore of the parasite itself [137,138].…”
Section: The Importance Of Dopamine and Other Neurotransmittersmentioning
confidence: 99%
“…This mechanism is produced by the induction in these cells of the GAD enzyme and therefore of GABA production and secretion, which in turn activate GABA receptors expressed by these same cells, stimulating their motility [137]. In experimental mouse models, inhibition of the GABAergic pathway by blockade of GABAA receptors or inhibition of the GAD enzyme markedly reduced the hypermotility and spread of T. gondii-infected dendritic cells and therefore of the parasite itself [137,138]. Finally, it has also been reported that brain infection by T. gondii can interfere with the GABAergic system by inducing changes in the distribution of the GAD67 enzyme, although this event has been related more to possible neurological complications of toxoplasmic encephalitis, such as seizures [139], than to possible complications of latent toxoplasmosis, such as schizophrenia.…”
Section: The Importance Of Dopamine and Other Neurotransmittersmentioning
confidence: 99%